158k views
3 votes

( \sin^(2) ( (\pi)/( 4 ) - \alpha ) ) = (1)/(2) (1 - \sin(2 \alpha ) )

Prove​

1 Answer

2 votes

Explanation:


\sin^2 ((\pi)/(4) - \alpha) = (1)/(2)(1 - \sin 2\alpha)

Use the identity


\sin^2 \theta = (1 - \cos 2\theta)/(2)

on the left side.


(1 - \cos [2((\pi)/(4) - \alpha)])/(2) = (1)/(2)(1 - \sin 2\alpha)


(1 - \cos ((\pi)/(2) - 2\alpha))/(2) = (1)/(2)(1 - \sin 2\alpha)

Now use the identity


\sin \theta = \cos((\pi)/(2) - \theta)

on the left side.


(1 - \sin 2\alpha)/(2) = (1)/(2)(1 - \sin 2\alpha)


(1)/(2)(1 - \sin 2\alpha) = (1)/(2)(1 - \sin 2\alpha)

User Northtree
by
6.1k points